162 Homocysteine level in patients with lupus nephritis. (April 2019) - Timlin, Homa
Abstract : Background: In SLE, both disease-specific and traditional risk factors are important. Increased serum homocysteine levels are seen in approximately 15% of patients with systemic lupus erythematosus and are associated with an increased risk of atherothrombotic events in this population. The serum level of homocysteine in patients with lupus nephritis has not been well described. Methods: We performed a retrospective review of patients who had both, a biopsy proven lupus nephritis (class II-VI), and measured homocysteine levels for the first time during routine evaluation. Clinical and laboratory data were obtained from review of medical records. Results: Five patients with lupus nephritis had homocysteine level measured. The ages ranged from 29–47 years and were predominately African Americans. There were two patients with class III, one with class III-V, one with class IV, and one with class V lupus nephritis. All were female, with positive anti-dsDNA, low C4 and on hydroxychloroquine. Of the five patients, all had elevated homocysteine levels. Conclusions: This study demonstrates that patients with lupus nephritis are at a high risk for developing elevated homocysteine levels. Funding Source(s): None